ON FORMING THE CORPUS OF INTERLINGUAL SEMANTIC CORRELATIONS FOR THE PURPOSES OF MULTILINGUAL EDUCATION IN NON-LINGUISTIC UNIVERSITIES - S.N. Rybkina (Многоязычие в образовательном пространстве)
The subject of this article is developing approaches for compiling a corpus of interlanguage semantic correlations, based on the vocabulary of the languages of the Indo-European family, stud-ied in non-linguistic universities, in order to prepare comparative textbooks on multilingual educa-tion. The use of linguogenetic and comparative methods of material analysis makes it possible to choose the English language as “a starting point” when compiling the corpus of interlanguage se-mantic correlations for the listed above purposes. It can be also done due to the genetic heterogene-ity of its lexical composition, which allows, on the one hand, to form correlations on the basis of common Indo-European and common Germanic vocabulary, and, on the other hand, on the basis of borrowings from different eras - the vocabulary of Romanic origin of the early Middle Ages (French-English vocabulary) and borrowings of later eras, included (in addition to English) into oth-er Indo-European languages (international vocabulary). Correlations within the named etymological groups are presented in the form of thematic series of vocabulary related to human life and the world around it. The relevance of referring to comparative studies in the lexical and semantic sphere is associated with the growth of their practical importance in connection with the situation of poly-glossia in modern non-linguistic universities and the need to improve the experience of teaching foreign languages vocabulary in the above mentioned conditions, based on the system and intersystem connections of the languages being studied.